(untitled) (Philological Studies, 2022)
This paper examines the usage and distribution of simple finite and non-finite verb forms in the headlines of articles in the electronic media in the RNM, in order to identify their specific morphological features in the Macedonian language, as well as their similarities and differences with other world languages as well. The sample consists of 50 randomly chosen headlines on the website time.mk, while data analysis and the findings are conducted with the use of the general qualitative interpretative/inductive method. The research results confirm the rare usage of imperative forms and the contribution of verbal nouns in the condensation of information, which is the main feature of headlines. With reference to the finite verb forms, the results suggest the more frequent use of the second meanings of the present simple tense, unlike the most frequent use of the first meanings of the past definite tenses (imperfect and aorist). Correspondingly, besides their own specific feature, the headlines in the Macedonian language show similarities with headlines in the English language.